Endocrown: indicação e seleção do material restaurador - Silva, Emilie Vicentin da [UNESP] (Universidade Estadual Paulista (Unesp), 2016)
Endodontically treated teeth have reduced rigidity and resistance due to loss of structural integrity. This fact can result in long-term problems of biomechanical failure, lack of elasticity and traction resistance of masticatory forces, it is not uncommon for more serious problems such as fractures occur. Therefore, the choice of functional and esthetic rehabilitation of these patient should be selected with caution, since the longevity of the endodontic treatment can be influenced by selection of the restorative material and a preparation that conserve as much healthy tooth structure. This course conclusion work is intended to present a brief review of literature about the subject endocrown and illustrate their performance with clinical case. This case showed that endocrown technique is indicated to posterior teeth, especially molars, which have short clinical crown and insufficient interocclusal space and be associated with adhesive ceramic. This is a procedure that aims at preserving tooth structure and harmonious esthetic results, in addiction to execute on less clinical sessions. The literature supports that compared to traditional crowns, the fracture resistance has to be superior. It is Important to note that the clinical success translated by longevity and comfort is dependent on the correct preparation and use of adhesive ceramic

Dentes tratados endodonticamente possuem redução da rigidez e resistência devido à perda da integridade estrutural. Este fato pode acarretar em longo prazo problemas de falhas biomecânicas, falta de elasticidade e de resistência à tração de forças mastigatórias, não sendo incomum que problemas mais graves como fraturas ocorram. Logo, a escolha da reabilitação funcional e estética desse paciente deve ser selecionada com muita cautela, já que a longevidade do tratamento endodôntico pode ser influenciada pela seleção do material restaurador e também de um preparo que conserve o máximo de estrutura dentária sadia. Este trabalho de conclusão de curso tem como objetivo apresentar uma breve revisão da literatura sobre o tema endocrown e ilustrar sua execução com caso clínico. O caso clínico evidenciou que a técnica endocrown está indicada para dentes posteriores, principalmente molares, que apresentem coroa clínica curta e espaço interoclusal insuficiente e estar associada às cerâmicas adesivas. Trata-se de um procedimento que visa à preservação da estrutura dental e resultados estéticos harmoniosos, além de executado em menos sessões clínicas. A literatura apoia que em comparação as tradicionais coroas totais, a resistência à fratura apresenta-se superior. É importante salientar que o sucesso clínico traduzido por longevidade e conforto é dependente do correto preparo e do uso das cerâmicas adesivas
Keywords: Coroa dentária; Dentes molares; Dente não vital; Tooth crown